Utilization Studies Library of Health Polytechnic Semarang - Warijan Warijan; Hermien Nugraheni; Hariyanti Hariyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
The purpose of this study is to identify the description of students' behavior in searching and using the information in the library of Ministry of Health Polytechnic Semarang. It is a descriptive study with cross sectional design which is not intended to test a specific hypotheses and merely describe a variable, symptoms or circumstances. The results shows that The Ministry of Health Polytechnic Semarang students who really need the library to support learning activities is 97 %. While 19% of students is also a member of another library outside the campus. The Ministry of Health Polytechnic Semarang library service is quite good, a statement proved by 54 % of respondents stated that the availability of literature in the library is adequate, 32 % of respondents say that they always find the necessary literature in the campus' library, 82 % of respondents say that the library's reading room is quite comfortable, and 84 % of respondents say that the library staff always manage to help the respondent difficulty in meeting their needs in the library .